Test beam measurement of ATLAS ITk Short Strip module at warm and cold operational temperature. (9th March 2023) - Arling, J.-H; Becot, C; Buchanan, E; Dopke, J; Gallop, B; Kaplon, J; Keller, J.S; Kroll, J; Li, Y; Li, Z; Liu, J; Liu, Y; et al.
Abstract: This study is focused on an investigation of the performance of the Short Strip module developed by the ATLAS Inner Tracker (ITk) strip collaboration using electron beams of energy 5.4 GeV and 5.8 GeV at the DESY-II Testbeam Facility. The noise at +30 °C and -30 °C was measured. The ratio of the two measurements is compared with a circuit-model calculation. The measured noise at -30 °C is compared with the maximum noise that would correspond to an acceptable signal-to-noise ratio after the expected radiation damage from operation at HL-LHC. The measured charge distributions at +30 °C and -30 °C are compared with GEANT4 simulations. The detection efficiency and noise-occupancy were measured as a function of threshold at both +30 °C and -30 °C. The average cluster width was measured as a function of threshold. Scans of detection efficiency versus threshold at different delay settings were used to reconstruct the pulse shape in time. The resulting pulse shape was compared with a circuit model calculation.